A study of the volatile oil extracted from the leaves of Cinnamomum mindanaense Elm (Fam. Lauraceae) - Verano, Ofelia Q.; Castillo, Amorita V. (Quezon City Department of Pharmacy, College of Pharmacy, University of the Philippines Diliman, 1972)
The volatile oil from the leaves of Cinnamomum mindanaense Elm. (Fam. Lauraceae) was extracted with steam using the Clevenger apparatus for heavier than water distillation. The air dried leaves was found to contain 0.4% of volatile oil.
The extracted oil showed similarity on its physical constanst with cinnamon leaf oil extract from Cinnamomum zeylanicum Nees (Fam. Lauraceae).
The oil was found to have a refractive index of 1.5331; specific gravity of 1.06; optical rotation of 0°29 (dextrorotatory); contained approximately 20% of aldehyde mostly cinnamic aldehyde and 65% of phenol namely, eugenol. The oil was soluble in twice its volume of 70% alcohol. A thin layer chromatography of the extracted oil showed the presence of 4 spots, the major spots which corresponded to the main constituents had the same Rf values as the reference standards, cinnemaldehyde and eugenol. UV spectroscopy was done for further analysis of the oil.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Diliman, 1972.
Keywords: Cinnamon; Essences and essential oils